Dental abnormalities after chemotherapy in long-term survivors of childhood acute lymphoblastic leukemia 7–40 years after diagnosis - Wilberg, Petter; Kanellopoulos, Adriani; Ruud, Ellen; Hjermstad, Marianne Jensen; Fosså, Sophie Dorothea; Herlofson, Bente Brokstad (Supportive care in cancer, 2016)
Purpose Factors associated with the long-term dental effects after chemotherapy for childhood malignancies have not been well described. The primary aims of this study were as follows: (1) to assess whether age at diagnosis and treatment-related factors are associated with dental defects in survivors of childhood acute lymphoblastic leukemia (ALL) and (2) to assess the survivors’ annual expenses for dental treatment compared to reference data. Methods This cross-sectional study enrolled 111 Norwegian survivors of ALL diagnosed before the age of 16. All of the subjects completed a questionnaire and underwent medical and oral examinations. Dental defects were registered according to the individual defect index, with 0 = no defects and 140 = anodontia, and the caries experience was registered according to the decayed-missing-filled teeth index (DMFT). Age-matched reference data were drawn from a national general population survey ( n = 555). Results The mean age at examination was 29.1 years (SD 7.2), and mean follow-up period was 22.9 years (SD 7.3). In a regression model, diagnoses occurring at ≤5 years of age ( B = −9.6, p < 0.001) and a cumulative dose of anthracyclines >120 mg/m 2 ( B = 11.5, p < 0.001) were strongly associated with more severe dental defects. Survivors treated after the age of 5 had experienced more caries than those treated at a younger age [DMFT 9.6 (SD 6.1) vs. 6.0 (SD 4.6), respectively; p = 0.001]. High annual expenses for dental treatment were reported by a larger percentage of the reference population compared to the survivor group (18 vs. 9 %, respectively; p = 0.02). Conclusions The age at diagnosis and the dose of anthracyclines appear to be strongly associated with the severity of dental defects, although few survivors reported high annual expenses for dental treatment. The increased risk of dental defects during adulthood should be communicated to ALL survivors.